STUDY OF TRITERPENE COMPOUNDS IN SHOOTS OF CRATAEGUS ALMAATENSIS POJARK (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The study of saponins, the results of the qualitative and quantitative content oftriterpene compounds in the shoots of Alma-Ata hawthorn was carried out. The presence oftriterpene compounds in the studied raw material was established using thin layer chromatography.The quantitative content of the sum of triterpene compounds was determined by spectrophotometry.As a result of qualitative reactions, triterpene saponins were found. After hydrolysis in the system:glacial acetic acid - hydrochloric acid - purified water (3.5: 1: 5.5) by thin layer chromatography,the sum of saponins was separated in the chloroform-methanol-water system (18: 11: 2.7). Ursolicacid was identified by spectrophotometry after the reaction of saponins with concentrated sulfuricacid at 317 nm, which in terms of conversion was 1.33%.
Keywords: shoots, Alma-Ata hawthorn, thin layer chromatography, spectrophotometry, triterpene compounds, ursolic acid.